Critical voices against the Bologna Process in Turkey: Neo-liberal governance in higher education. (11th June 2015) - Kaya, Ayhan
Abstract: This article analyzes critical voices raised against the Bologna Process by various stake-holders of higher education in Turkey, such as rectors, professors, international office staff, students, and civil society organizations. The data collected through in-depth interviews were analyzed using the discourse analysis method on the basis of the interlocutors' reflections on the Bologna Process. It is claimed in the article that most universities in Turkey have attempted a process of internationalization and institutionalization, but that there have been several impediments during the implementation of the Bologna Process. Rising Euroskepticism in Turkey has also changed the process of Europeanization in the universities. It is revealed that the structural changes made in line with the Bologna Process are perceived by several different stake-holders as neo-liberal acts, and are presented as activities of internationalization, but not of Europeanization.